GAMBARAN TINGKAT PENGETAHUAN MASYARAKAT TENTANG BANTUAN HIDUP DASAR (BHD) DI WILAYAH KERJA UPTD PUSKESMAS JATILUHUR PURWAKARTA - Wirdan Fauzi Rahman; Serly, Serly; Siva Salsabila (Journal of Innovation Research and Knowledge, 2024)
Hospitalization can cause anxiety and stress in children while being treated in hospital. Anxiety is a response to something that is influenced by negative feelings about oneself, excessive fear is defined as feelings of anxiety. World Health Organization (WHO), the percentage of children undergoing hospitalization reaches 45%. Based on data taken from interviews with the Head of the Room and the parents of children at the Karawang Regional Hospital, the prevalence of children who experience anxiety levels is 85%, in children aged 4 years 80% every year children experience anxiety when they are in a new environment and are afraid of it. farewell. Brain gym is an activity that can stimulate the brain through a series of simple body movements and is carried out regularly every day and is useful for increasing human brain activity. This research uses observation sheets and HARS scale assessment sheets. The subject used was a 4 year old child who experienced levels of anxiety. Based on research in An. A conclusion was obtained, namely the results of the first assessment with a score of 27 in the moderate anxiety category. After implementing brain gym therapy for 3 days, changes occurred until the last day to a score of 14 in the mild anxiety category. So it can be concluded that brain gym therapy is effective in reducing anxiety levels in children